"Maternal thinking" and the concept of "vulnerability" in security paradigms, policies, and practices. (February 2014) - Cohn, Carol
This article takes as its starting point Sara Ruddick's discussion of "vulnerability" in her 1989 groundbreaking book Maternal Thinking: Toward a Politics of Peace . It examines the kind of thinking about vulnerability that Ruddick describes as developed through maternal practice and uses it as a heuristic device for rethinking the conceptions of and responses to vulnerability that permeate national and international security discourses. It explores the specific forms of practice and reason that are implicated by these different stances toward vulnerability and shows that the (often unexamined) assumptions underlying these stances are profoundly consequential for both policy and practice. Specifically, it takes both nuclear weapons and the so-called Global War on Terror as particular forms of response to perceived vulnerability and scrutinizes the practices associated with each in light of the forms of rationality arising from maternal practice. It also explores the assumptions underlying the concept of "vulnerable groups" commonly employed in international policy institutions, teasing out their implications for politics, policy, and action. Overall, it argues that Ruddick's articulation of maternal thinking provides a valuable resource for reimagining transformed and transformative security practices.